Characterization of Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov. and illumination of the distinct adaptative strategies of the genus Maribacter - Gao, Jia-Wei; Ying, Jun-Jie; Dong, Han; Liu, Wen-Jia; He, Dong-Yan; Xu, Lin; Sun, Cong (Frontiers in Marine Science, 2023)
Polysaccharides are complex carbohydrates and are abundant in the marine environment. Microbes degrade and utilize them using Carbohydrate-active enzymes (CAZymes), which mediate polysaccharides into the marine carbon cycle. With the continued supply of polysaccharides from the marine environment, tidal flats are also abundant in polysaccharides, resulting in an abundance of marine polysaccharide degrading strains. In this study, three novel strains, designated as D37T, M208T, and SA7T, were isolated from the intertidal sediment samples located in Zhoushan, Zhejiang and Huludao, Liaoning, PR China. The phylogenetic trees using the 16S rRNA gene and genome sequences showed that the three novel strains belonged to the genus Maribacter. The highest 16S rRNA gene sequence similarities between the three novel strains and other strains of the genus Maribacter were 98.7%, 99.2%, and 98.8%, respectively, while the ANI, AAI, and dDDH values between the three strains and the other strains of the genus Maribacter were 70-86%, 67-91%, and 17-30%, respectively, supporting their affiliation as novel species. Combined with other phenotypic and genotypic characterization in this study, three novel species are proposed as Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov., respectively, for the three strains. Furthermore, we compared all available genomes of Maribacter representatives and found that Maribacter strains could be divided into two groups (A and B). The two groups are different in genome size and G + C content and gene densities of CAZyme, peptidase, and sulfatase. Group A possesses more CAZymes which are related to degrading laminarin, fucoidan, mannan, xylose, and xylan. This result suggests that the two groups may have different niche adaptation strategies. Our study contributes to a better understanding of the role of marine flavobacteria in biogeochemical cycles and niche specialization.